The radiation hardness of certain optical fibres for the LHC upgrades at -25°C - Issever, C; Hanzlik, J; Huffman, B; Weidberg, A (2009)
A luminosity upgrade is planned in the future for the Large Hadron Collider at CERN (called SLHC). Two optical fibres have been tested in a bespoke cold container achieving a constant temperature of ≃ -25°C during the entire exposure. The motivations and results of these tests are presented and two mul-timode and one single mode optical fibre have been identified as candidates for optical links within the joint ATLAS and CMS Versatile Link project.